A pilot study of fluticasone propionate in untreated coeliac disease. Issue 3 (March 1991) - Mitchison, H C; al Mardini, H; Gillespie, S; Laker, M; Zaitoun, A; Record, C O
Abstract : Although gluten withdrawal is likely to remain the mainstay of treatment for adult coeliac disease, many patients find the diet inconvenient and unpalatable and compliance among asymptomatic patients is often poor. Oral corticosteroids have been used for patients who seem to be resistant to gluten withdrawal but preparations with low systemic bioavailability might be preferable. We have given a new glucocorticoid (fluticasone propionate) to 12 adults with untreated coeliac disease for six weeks while they were on a normal diet. One patient defaulted and one suffered a relapse in a pre-existing neoplasm. Excluding these, there was an improvement of symptoms, a mean weight gain of 2 kg, and a rise in albumin of 5.4 g/l. There was a significant improvement in the lactulose/mannitol excretion ratio (p less than 0.05) and in all histological variables examined in paired biopsy specimens (surface and crypt intraepithelial lymphocyte/enterocyte and goblet cell/enterocyte ratios and enterocyte height, p less than 0.01 or better). In six paired specimens sucrase and alkaline phosphatase activity increased in all (p less than 0.05) and lactase in five of six. No appreciable side effects were observed, but two patients had suppressed cortisol values and synacthen responses at six weeks. A further three, with normal pretrial results, had a blunted tetracosactrin response at six weeks. Fluticasone propionate seems worthy of further assessment in the treatment of coeliac disease as an adjunct to gluten withdrawal.